Low sensitivity of histopathological examination of peri-implant tissue samples in diagnosing postoperative spinal implant infection. (July 2020) - Bürger, Justus; Palmowski, Yannick; Strube, Patrick; Perka, Carsten; Putzier, Michael; Pumberger, Matthias
Abstract : Aims: To evaluate the histopathological examination of peri-implant tissue samples as a technique in the diagnosis of postoperative spinal implant infection (PSII). Methods: This was a retrospective analysis. Patients who underwent revision spinal surgery at our institution were recruited for this study. PSII was diagnosed by clinical signs, histopathology, and microbiological examination of intraoperatively collected samples. Histopathology was defined as the gold standard. The sensitivity for histopathology was calculated. A total of 47 patients with PSII and at least one microbiological and histopathological sample were included in the study. Results: PSII occurred in approximately 28% of the study population. Histopathology showed a sensitivity of 51.1% in the diagnosis of PSII. The most commonly found pathogens were Cutibacterium acnes and gram-positive staphylococci . Conclusion: Histopathology has low sensitivity for detecting PSII. In particular, infections caused by low-virulence microorganisms are insufficiently detected by histopathology. Cite this article: Bone Joint J 2020;102-B(7):899–903.